Penanaman Nilai-Nilai Pendidikan Karakter Melalui Pendidikan Agama Buddha Siswa Kelas I SD Sekolah Minggu Buddha Mandala Maitreya Pekanbaru - Suleska, Suleska; Rida Jelita (STAB Maitreyawira, 2025)
This study aims to describe the process of instilling character education values ​​through Buddhist Religious Education to grade 1 elementary school students at the Mandala Maitreya Buddha Sunday School in Pekanbaru. The background of this study is the importance of character formation from an early age, especially through religious education that is able to instill moral, ethical, and spiritual values. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through observation, interviews, and documentation. Based on the results of the study, it can be concluded that the instillation of character education values ​​through Buddhist Religious Education learning for grade 1 elementary school students at the Mandala Maitreya Buddha Sunday School in Pekanbaru is carried out systematically and enjoyably. The character values ​​that are instilled include love, discipline, responsibility, and respect. The instillation process is carried out through the Dhamma story method, Buddhist chants, Puja Bakti activities, and good behavior practices in everyday life. Supporting factors in this process include the role of teachers as role models, parental support, a conducive learning environment, and interesting learning methods. However, there are also several inhibiting factors, such as limited understanding of early childhood students, limited learning duration, lack of supporting facilities, and lack of consistency in the application of values ​​in the family environment.